A Drug Review on Cheppu Nerunjil Ennai-A Siddha Herbal Formulation in the Management of Sooli Kanam (Childhood Asthma) In Children - Brindha. A,; Meenakshi Sundaram.M,; Meenakumari.R, (International Journal of Ayurveda and Pharma Research, 2021)
Siddha system is the oldest and well documented Indian traditional System of medicine. The term Siddha means achieving perfection. Siddhars were saints who achieved better results in medicine. Siddhars are human beings with super intellectual capacity. Asthma is one of the most common chronic diseases of childhood. Most children develop asthma in early age. Prevalence of asthma in children increases due to growing urbanization, modernization, overcrowding and changing lifestyles. Asthma is a non communicable disease characterized by recurrent wheezing, breathlessness, chest tightness, and coughing. The symptoms of Soolikanam nearly correlate with childhood asthma. Numerous medicines for Soolikanam (childhood asthma) are explained in Siddha text. Cheppu Nerunjil Ennai is one of the herbal formulations indicated for Soolikanam. Cheppu nerunjil ennai was mentioned in Balavagadam siddha text book. This trial drug Cheppu Nerunjil Ennai comprises of eight herbal ingredients like Indigofera linnaei, Desmodium triflorum, Euphorbia parviflora, Cassia tora, Vigna trilobata, Sesbania grandiflora, Allium cepa. The herbal ingredients of Cheppu Nerunjil Ennai possess anti asthmatic activity, anti spasmodic, anti allergic activity, anti oxidant and immunomodulatory activity. This review article reflects history, properties, chemical constituents, pharmacological activities and several medicinal uses of the drug Cheppu Nerunjil Ennai on Soolikanam. This review further focuses to improve the research on Siddha herbal medicines.